2001
DOI: 10.1002/hed.1144
|View full text |Cite
|
Sign up to set email alerts
|

Cervical nodal metastases in squamous cell carcinoma of the head and neck: What to expect

Abstract: The treatment and management of malignancies of the head and neck is directly altered by the presence of metastatic cervical adenopathy. The treatment of nodal metastases in squamous cell carcinoma of the head and neck (HNSCCA) is determined by the lymphatic drainage of the upper aerodigestive tract. The lymphatic drainage is site-specific and occurs in a predictable manner. The purpose of this text is to provide an overview of the normal routes of lymphatic drainage in the head and neck and correlate this wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
95
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(102 citation statements)
references
References 8 publications
2
95
0
5
Order By: Relevance
“…This corresponds to the findings of Mukherji and others who found that oral tongue and floor-of-mouth cancers have an expected drainage to contralateral nodal basins in up to 9% of cases. 13 The site of oral tongue cancers may play a factor in the risk of contralateral metastases since the lymphatic drainage may differ in different areas of the oral tongue, but the numbers in the current study are too small to draw conclusions. The work of Mukherji and others also suggests that tongue and floor-of-mouth tumors have a similar risk of contralateral nodal involvement.…”
Section: Discussionmentioning
confidence: 90%
“…This corresponds to the findings of Mukherji and others who found that oral tongue and floor-of-mouth cancers have an expected drainage to contralateral nodal basins in up to 9% of cases. 13 The site of oral tongue cancers may play a factor in the risk of contralateral metastases since the lymphatic drainage may differ in different areas of the oral tongue, but the numbers in the current study are too small to draw conclusions. The work of Mukherji and others also suggests that tongue and floor-of-mouth tumors have a similar risk of contralateral nodal involvement.…”
Section: Discussionmentioning
confidence: 90%
“…En una revisión de los principales trabajos publicados al respecto, se obtuvo el patrón de diseminación y la frecuencia de compromiso metastásico cervical subclínico según el sitio primario de 428 pacientes sometidos a disección cervical electiva (N0) 10 . Los resultados se resumen en la Tabla 3.…”
Section: Metástasis No Detectables Clínicamenteunclassified
“…Therefore, it is reasonable to attempt to decrease the probability of carotid artery stenosis and other adverse effects by IMRT with a reduced CTV, if possible [20]. Lymphatic drainage of carcinomas of the head and neck has been associated with the primary tumour location and adjacent subsites to which the tumour has spread [21]. In the case of NPC, the lymphatic vessels of the nasopharynx drain in two general directions, lateral and medial [22].…”
Section: Nodal Metastasis In Nasopharyngeal Cancermentioning
confidence: 99%